Association between serum mineral concentrations and gastrointestinal parasite burden in zebu cattle accessing ‘hora’ mineral water in southwestern Ethiopia - Ashenafi Miresa; Taye Tolemariam; Belay Duguma; Ellen S. Dierenfeld; Abebe Nigussie; Feyissa Begna (PLoS ONE, 2025)
Gastrointestinal parasites (GIP) and mineral deficiencies are significant factors affecting health and productivity of free-ranging cattle. Adequate mineral intake, particularly from natural mineral water sources (hora), is vital for immune function, gastrointestinal health, and nutrient absorption. This study aimed to explore the association between GIP burden and serum mineral concentrations in zebu cattle (Bos indicus) routinely accessing hora mineral water in southwestern Ethiopia. A total of 180 fecal samples were collected from cattle across four districts (Bedele, Dabo, Gechi, and Borecha) and analyzed qualitatively and quantitatively to determine parasite presence and fecal egg count. Concurrently, blood samples were collected to evaluate serum mineral concentrations. The overall GIP prevalence was 55.6%, with Strongyle-type nematodes being the dominant GIP group. Gechi district showed the highest prevalence (64.4%) and mean egg per gram (EPG) of 212.8 (p < 0.05). Although, serum mineral concentrations were generally adequate, significant variations were observed across districts. Strong negative correlations (p < 0.05) were observed between EPG and serum concentrations of zinc (Zn), manganese (Mn), iron (Fe), and copper (Cu), indicating that adequate intake of these minerals, potentially sourced from the hora mineral water, may be associated with improved resistance to parasitic infections. These negative correlations were supported by negative binomial regression analysis which identified Zn as the strongest predictor of EPG. Overall, the findings highlight the importance of hora as a natural mineral supplement in its association with lower GIP burden in free-ranging zebu cattle. While this study indicates a correlation between serum mineral concentrations and GIP burden in grazing cattle, controlled experiments are essential to determine the specific effects of individual minerals found in hora on parasite resistance and establish causality.